Understanding the mobility chances of children from working-class backgrounds in Britain: how important are cognitive ability and locus of control? - Betthäuser, BA; Bourne, M; Bukodi, E (Wiley, 2020)
Research in social stratification has shown that children from working‐class backgrounds tend to obtain substantially lower levels of educational attainment and lower labor market positions than children from higher social class backgrounds. However, we still know relatively little about the micro‐level processes that account for this empirical regularity. Our study examines the roles of two individual‐level characteristics—cognitive ability and locus of control—in mediating the effect of individuals’ parental class background on their educational attainment and social class position in Britain. We find that cognitive ability mediates only about 35% of the total parental class effect on educational attainment and only about 20% of the total parental class effect on respondents’ social class position, net of their educational attainment. These findings contradict existing claims that differences in the life chances of children from different social class backgrounds are largely due to differences in cognitive ability. Moreover, we find that although individuals’ locus of control plays some role in mediating the parental class effect, its role is substantially smaller than the mediating role of cognitive ability. We measure individuals’ social class positions at different points in their careers—at labor market entry and at occupational maturity—and find that the mediating roles of cognitive ability and locus of control are remarkably stable across individuals’ working lives.